Implementation Curriculum Merdeka Belajar Learn Science And Social (Ipas) Learning In Elementary School: Perpective Teacher - Sulistyani Ramadhani (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Effective and relevant learning plays a key role in improving the quality of education in this modern era. One concept that is currently developing is